A roadmap for ladybird conservation and recovery - Soares, António O.; Haelewaters, Danny; Ameixa, Olga M. C. C.; Borges, Isabel; Brown, Peter M. J.; Cardoso, Pedro; de Groot, Michiel D.; Evans, Edward W.; Grez, Audrey A.; Hochkirch, Axel; Holecová, Milada; Honěk, Alois; et al. (Conservation biology, 2023)
Ladybirds (Coleoptera: Coccinellidae) provide services that are critical to food production, and they fulfill an ecological role as a food source for predators. The richness, abundance, and distribution of ladybirds, however, are compromised by many anthropogenic threats. Meanwhile, a lack of knowledge of the conservation status of most species and the factors driving their population dynamics hinders the development and implementation of conservation strategies for ladybirds. We conducted a review of the literature on the ecology, diversity, and conservation of ladybirds to identify their key ecological threats. Ladybird populations are most affected by climate factors, landscape composition, and biological invasions. We suggest mitigating actions for ladybird conservation and recovery. Short‐term actions include citizen science programs and education, protective measures for habitat recovery and threatened species, prevention of the introduction of non‐native species, and the maintenance and restoration of natural areas and landscape heterogeneity. Mid‐term actions involve the analysis of data from monitoring programs and insect collections to disentangle the effect of different threats to ladybird populations, understand habitat use by taxa on which there is limited knowledge, and quantify temporal trends of abundance, diversity, and biomass along a management‐intensity gradient. Long‐term actions include the development of a worldwide monitoring program based on standardized sampling to fill data gaps, increase explanatory power, streamline analyses, and facilitate global collaborations. Resumen Las catarinas (Coleoptera: Coccinellidae) proporcionan servicios que son críticos para la producción de alimento, y juegan un papel ecológico como fuente de alimento para depredadores. Sin embargo, la riqueza, abundancia y distribución de catarinas están en peligro debido a muchas amenazas antropogénicas. La carencia de conocimiento sobre el estatus de conservación de la mayoría de las especies y los factores que inciden en su dinámica poblacional dificulta el desarrollo e implementación de estrategias de conservación para las catarinas. Realizamos una revisión de la literatura sobre la ecología, diversidad y conservación de catarinas para identificar sus amenazas ecológicas clave. Las poblaciones de catarinas fueron afectadas mayormente por factores climáticos, composición del paisaje e invasiones biológicas. Proponemos acciones de mitigación para la conservación y recuperación de catarinas. Acciones a corto plazo incluyen programas de ciencia y educación ciudadana, medidas de protección para la recuperación de hábitat y de especies amenazadas, prevención de la introducción de especies no nativas y el mantenimiento y restauración de áreas naturales y la heterogeneidad del paisaje. Acciones a mediano plazo implican el análisis de datos obtenidos de programas de monitoreo y colecciones de insectos para desenmarañar el efecto de las diferentes amenazas a las poblaciones de catarinas, comprender el uso del hábitat por taxa de los que se tiene conocimiento limitado y cuantifica las tendencias temporales de la abundancia, diversidad y biomasa a lo largo de un gradiente de intensidad de manejo. Acciones a largo plazo incluyen el desarrollo de un programa de monitoreo a nivel mundial basado en muestreos estandarizados para subsanar la falta de datos, incrementar el poder explicativo, optimizar los análisis y facilitar colaboraciones globales. Article impact statement: In light of major ecological threats, mitigating actions at different timescales are crucial for ladybird conservation and recovery. 【摘要】 随着世界范围内人类与野生动物的冲突不断升级, 对野生动物的宽容和接纳等概念变得越来越重要。然而, 当代保护研究表明, 人们对人类与野生动物积极互作的认识有限, 导致可能难以准确描述人类与动物的相遇。如果不解决这些局限性, 就会导致野生动物和景观管理计划的设计和实施存在不足, 以及对本土生态知识的否定。我们利用印度喀拉拉邦瓦亚纳德野生动物保护区森林中的阿迪瓦西族Kattunayakans部落的民族志证据, 来研究印度原住民对于人类与野生动物共存的观点。通过定性的实地研究(包括访谈和在森林样带调查), 我们发现Kattunayakans部落表现出对野生动物的宽容和接纳, 其特点是深入的共存, 包括三个中心思想:野生动物是有理性的交流者;野生动物是神、老师和平等的族群;野生动物是实行 “dharmam”的具有共同起源的亲戚。我们认为, 充分理解以上几点有助于将Kattunayakan部落的观点引入印度的森林管理, 并更广泛地解决人类与野生动物的冲突。